The complete chloroplast genome sequence of Rhaponticum uniflorum, the first of the genus Rhaponticum. Issue 1 (2nd January 2022) - Boqin, Hu; Zhou, Qiang; Wang, Liqiang; Jiang, Mei; Gong, Guohua; Liu, Chang; Wei, Chengxi
Abstract: Rhaponticum uniflorum is commonly used as a source for traditional medicines with the main effect of clearing heat. Here, we sequenced the complete chloroplast (cp) genome of R. uniflorum to develop molecular markers for taxonomic classification and species determination of R. uniflorum . It was 152, 760 bp in size and has a typical circular structure, including a pair of inverted repeats with 25, 205 bp, a large single-copy region with 83, 687 bp, and a small single copy region with 18, 663 bp. The genome encodes 110 unique genes, including 80 protein-coding, four rRNA and 26 tRNA genes. Phylogenomic analysis shows that R. uniflorum is closely related to the Saussurea . The study is useful for phylogenetic and population genetic studies of Rhaponticum plants.